GENDER SENSITIVE MESSAGES DELIVERED IN THE DISNEY MOVIE FROZEN - Retno Muljani; Mega Wulandari; Deasy Ekawati (Universitas Sanata Dharma, 2018)
In the era of information technology, electronic media are broadcasted throughout the world by farreachingmultinational companies. In that way, various forms of entertainment have becomeinseparable from childrens daily lives. Due to their extensive presence, media may have considerableinfluence over childrens development and behaviour. Naturally, media are expected to provide notonly creative entertainments but also positive didactic messages for child viewers, including thoseunder five (5) years old. Early age education practitioners can make use of the movies to introducethe child viewers to certain values such as relevant gender sensitive messages. Frozen (2013) is amovie which depicts female independent characters that do not pursue romance as their only lifegoal; instead, they prefer to stay together and keep their mutual love as sisters after a long journeyfull of adventures.In this preliminary study, the visual and narrative elements of the movie are studiedin order to analyze the gender sensitive messages wrapped in entertaining styles. To some extent,themessages can also enhancefive different developmental domains of childrennamely social, physical,intellectual, creativity, and emotion development (in short, S.P.I.C.E.).Thus, watching the movie canbring benefits to child and adult viewers from the viewpoints of entertainment, education, and childdevelopment.